Removal of retained subretinal perfluorocarbon liquid. Issue 12 (24th November 2008) - García-Arumí, J; Castillo, P; López, M; Boixadera, A; Martínez-Castillo, V; Pimentel, L
Abstract : Aim: To report a case series in which a modified technique was used to remove retained subretinal perfluorocarbon liquid. Method: In three patients with retained subretinal perfluorocarbon liquid, a three-port pars plana vitrectomy approach was used to perform a small self-sealing retinotomy adjacent to the perfluorocarbon liquid bubble. The tip of a 50-G glass micropipette connected to an active suction system was inserted in the bubble, and the liquid was aspirated. Results: Successful removal of subretinal perfluorocarbon liquid was achieved in all cases with no complications. Visual acuity improved in all patients. Conclusion: With the technique presented, retained subretinal perfluorocarbon liquid can be successfully removed with minimal trauma to adjacent tissues.